IT skills for successful study - Clarke, Alan (New York Palgrave Macmillan, 2005)
Here is a guide to help students exploit IT to aid their studies. It demonstrates how information and communication technologies can help with writing, analysis, research, communication and presentation. Most students will know how to word process but not how to exploit word processing applications to write longer documents, add footnotes, insert tables, create indexes, track changes, or add figures, and may have not used a spreadsheet to analyze data. Focusing on Microsoft Office programs, this book will help students develop intermediate or advanced IT skills in those areas most relevant to studying.